Microplastics in the environment: A critical review of current understanding and identification of future research needs - Akdogan, Zeynep; Guven, Basak (Environmental pollution (1987), 2019)
Microplastics (plastic particles <5 mm) are a contaminant of increasing ecotoxicological concern in aquatic environments, as well as for human health. Although microplastic pollution is widespread across the land, water, and air, these environments are commonly considered independently; however, in reality are closely linked. This study aims to review the scientific literature related microplastic research in different environmental compartments and to identify the research gaps for the assessment of future research priorities. Over 200 papers involving microplastic pollution, published between 2006 and 2018, are identified in the Web of Science database. The original research articles in ‘Environmental Sciences’, ‘Marine/Freshwater Biology’, ‘Toxicology’, ‘Multidisciplinary Sciences’, ‘Environmental Studies’, ‘Oceanography’, ‘Limnology’ and ‘Ecology’ categories of Web of Science are selected to investigate microplastic research in seas, estuaries, rivers, lakes, soil and atmosphere. The papers identified for seas, estuaries, rivers and lakes are further classified according to (i) occurrence and characterization (ii) uptake by and effects in organisms, and (iii) fate and transport issues. The results reveal that whilst marine microplastics have received substantial scientific research, the extent of microplastic pollution in continental environments, such as rivers, lakes, soil and air, and environmental interactions, remains poorly understood. [Display omitted] •Knowledge of microplastic fate and transport in the environment is still limited.•Microplastic transport between environmental matrices should be considered.•There is a need for watershed scale investigation of microplastics.